Studies on the Effect of Water Stress on Root Traits in Redgram Genotypes - Amarapalli, Geetha (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during July–November, 2019 at Regional Agriculture Research Station, Professor Jayashankar Telangana State Agricultural University, Palem, Nagarkurnool district, Telangana State, India. The main treatments had five red gram genotypes and water stress levels were taken as sub-treatment in 3 replications in factorial RBD using specialized root structure made with cement bricks. There was great variability in the yield performance of different Redgram genotypes under drought conditions. The experiment was conducted to select genotypes with efficient root architecture and associated traits under drought stress. Root studies were performed with the Delta T automatic root scanner. The SPAD chlorophyll meter was used to measure the SCMR value. The present study results revealed that genotype, Maruti showed significant superiority for character plant height and SCMR under non-stress, mild stress and severe stress conditions. The same genotype showed superior values for main root length under control and mild stress. Whereas, Laxmi recorded the highest plant height under severe stress and the same genotype also showed significant superiority for total plant dry weight, root dry weight and root area under severe stress. The genotype Laxmi showed significant character, root area and diameter superiority under mild stress. ICPL-20176 recorded significant superiority for main root length under severe stress and root tip for mild stress. The identified genotypes can be used as the parents in future drought-proof breeding useful for cultivating in water stress conditions.